2002
DOI: 10.1063/1.1489481
|View full text |Cite
|
Sign up to set email alerts
|

Small band gap bowing in In1−xGaxN alloys

Abstract: High-quality wurtzite-structured In-rich In1−xGaxN films (0⩽x⩽0.5) have been grown on sapphire substrates by molecular beam epitaxy. Their optical properties were characterized by optical absorption and photoluminescence spectroscopy. The investigation reveals that the narrow fundamental band gap for InN is near 0.8 eV and that the band gap increases with increasing Ga content. Combined with previously reported results on the Ga-rich side, the band gap versus composition plot for In1−xGaxN alloys is well fit w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

31
333
5
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 605 publications
(373 citation statements)
references
References 25 publications
31
333
5
4
Order By: Relevance
“…It has been discovered recently that wurtzite-structure InN is actually a narrow gap semiconductor, with a minimum bandgap energy equal to ~ 0.77 eV [ 4,5]. The studies of In-rich InGaN have shown that the optical properties of these alloys are consistent with the observed narrow gap of InN, and wit h the relatively high luminescence efficiency as it is found in the Ga-rich InGaN alloys [5,6]. The bandgap of the InGaN ternary system thus covers a very wide range of the optical spectrum from the infrared for InN to the ultraviolet for GaN.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…It has been discovered recently that wurtzite-structure InN is actually a narrow gap semiconductor, with a minimum bandgap energy equal to ~ 0.77 eV [ 4,5]. The studies of In-rich InGaN have shown that the optical properties of these alloys are consistent with the observed narrow gap of InN, and wit h the relatively high luminescence efficiency as it is found in the Ga-rich InGaN alloys [5,6]. The bandgap of the InGaN ternary system thus covers a very wide range of the optical spectrum from the infrared for InN to the ultraviolet for GaN.…”
mentioning
confidence: 89%
“…The bandgap bowing in group III nitride alloys was found to be proportional to the bandgap difference between the end-point compounds. InGaN, [6] InGaN, [11] InGaN, [12] InAlN, this work InAlN, [7] AlGaN, this work fit, β=0.54 abs, this work abs, [7] PL, this work InGaN, [6] InGaN, [12] InGaN, [11] InAlN, [7] InAlN, this work GaAlN, this work …”
mentioning
confidence: 99%
“…1 The band gap of the In x Ga 1-x N alloy system now spans the entire optical window from the near infrared to the UV. 2 Most experimental studies have focused on the optical properties of the band gap and there is a general paucity of spectroscopic measurements of the valence and conduction band densities of states in InN. Recently, the first combined x-ray photoemission spectroscopy (XPS) measurements and density functional theory (DFT) calculations of the valence band structure of single crystalline wurtzite InN have been reported.…”
mentioning
confidence: 99%
“…[17][18][19] Recent photoluminescence studies indicate the band gap of InN may be as small as 0.7-0.8 eV. [20][21][22] Depending on the value chosen for the band gap in Eq. ͑2͒, the surface barrier height of Au on annealed InN could either be considered to be essentially zero or 1.2Ϯ0.1 eV.…”
mentioning
confidence: 99%